Indigenous Segregation in Metropolitan Zones at Hidalgo State, México 2010-2020: Urban spatial distribution patterns in metropolitan contexts - Ramírez-Avilés, José Iván (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper’s goal is to analyze the spatial distribution of the indigenous population at a metropolitan level, identifying possible spatial patterns of segregation, by using the Index of Areal Segregation (ISEA) and the Local Moran Index. The first step to do this is through approximation and analysis of census variables that measure the use of language and belonging to indigenous households. The main results indicate that there are urban spaces with a segregated indigenous population, although with different scenarios and spatial distribution characteristics, some more centralized, others in interstices and with dispersion in the peripheries.